A Review of the Modern Mongolian Healthcare System - Neumann, Natalie; Warburton, David (Central Asian Journal of Medical Sciences, 2015)
Objectives: Known to most as the horse-loving homeland of Chinggis Khan, Mongolia is today a country of increasing geopolitical, economic, and popular cultural significance. But even as an increasing number of health workers visit the country, its healthcare system remains unexplored in the medical literature. Here follows a broad-brushstrokes overview of the modern medical system of Mongolia, its structure and challenges. It is comprised of an overview of the country’s demographics, health profile, and medical history, followed by a brief summary of selected issues that affect the modern healthcare system. Methods: Descriptive single-case study consisting of clinical observations by the authors, original hospital-level data, and interviews with practitioners and policymakers. Results: The Mongolian healthcare system has performed well through the tumultuous transition from a socialist to a capitalist economy. Our analysis reveals three areas that require improvement: delivery of care, practitioner experience, and health systems administration. Conclusion: This article reviews not only the history and structure of the modern Mongolian healthcare system, but also its strengths and challenges. It is hoped that in explicating these issues, current and future efforts to assist Mongolian health-care providers may be directed more constructively and efficiently.